Study on the Influence of Toilet Siphon Pipe Shape on Flushing Performance - Xiaole Ge; Hongfeng Wang; Zhanfu Li; Shengrong Liu; Xin Tong; Jiafei Pu; Qi Dong (Journal of Engineering and Technological Sciences, 2020)
The goal of this work was to explore the influence of toilet siphon pipe shape on flushing performance. The flushing processes of a toilet under different shape parameters were simulated by using computational fluid dynamics (CFD) with a volume of fluid (VOF) multiphase model. The effects of siphon pipe shape on flushing performance were analyzed in detail. The interpretation of the simulation results was experimentally validated. The results reveal that a toilet may obtain good flushing performance under one single shape parameter when the climbing angle, the arc width, the arc height, the pipe diameter, the climbing width, and the climbing height are about 48°, 45 mm, 210 mm, 50 mm, 90 mm and 30 mm, respectively. With the increase of the siphon pipe diameter, the toilet flushing performance peaks in the range between 50 and 53 mm rather than continuing to improve. In order to reasonably evaluate the flushing effect of the toilet, all ï¬‚ow parameters on a characteristic cross section of the siphon pipe, including the average velocity, the average pressure and the average mass flow rate, should be comprehensively considered instead of one single parameter. The findings of this study provide a reference for the pipe shape design of toilets.